Knowledge, attitudes, and barriers regarding health promotion of ovarian cancer among community pharmacists in Jordan - Khaled Alrosan; Mohanad Odeh; Tahani Alwidyan; Amjad Z Alrosan; Saba Madae’en (Future Science OA, 2025)
BackgroundOvarian cancer is the most lethal gynecological cancer in women, which is characterized by nonspecific symptoms that delays its diagnosis until advanced stages, thus it has been called the silent killer disease. Since community pharmacists are easily accessible healthcare providers, and because of their roles in health promotion activities and disease prevention services; this study was conducted to better understand their knowledge, attitudes, and challenges toward ovarian cancer health promotion.Methods An internet-based self-administrated questionnaire was distributed to community pharmacists in Jordan (n = 194) with a response rate of 53.9% through an online platform.Results About 75.2% of the community pharmacists had insufficient knowledge score of ovarian cancer and 58.2% had a higher-positive attitude. There was a significant association between the community pharmacist knowledge score and the work status or the education level (p < 0.05). The perceived lack of pharmacist’ s knowledge and the absence of a private area in pharmacies for confidential conversations represent the major barriers (72.1% and 69.6%, respectively).Conclusion Despite limited knowledge about the symptoms and risk factors of ovarian cancer, as well as barriers hindering the full realization of community pharmacists’ roles, they demonstrated a positive attitude toward educating patients about ovarian cancer health.